NON-HODGKIN'S LYMPHOMAS OF FEMALE REPRODUCTIVE SYSTEM - A. V. Babkina; B. O. Toloknov; O. V. Kamaeva; I. I. Bokin; A. R. Shafiev; I. V. Poddubnaya (Опухоли женской репродуктивной системы)
Non-Hodgkin's lymphomas are extremely rare among all tumors of female reproductive system. Diagnostic mistakes and inadequate therapeu- tic tactics in these diseases are results of usual absence of alertness of gynecologists. The aims are to analyze reasons of diagnostic mistakes in patients with non-Hodgkin's lymphomas of female reproductive system and to discover definitive clinical and morphological characteristics of female reproductive system lymphoid tumors. During the period between 1989 and 2006, 305 cases of primary extranodal non-Hodgkin's lym- phomas were detected; female reproductive system was affected in 7% of patients (totally 40 patients), which were included in investigated group. In the whole analyzed group of women (n=40, median age 43 yrs, range 17-84 yrs), patients with primary lesion of female reproductive system had median age of 40 yrs and with secondary involvement - 46 yrs. Most of patients were fertile (60%, n=24). Such tumors was localized in breast in 40% of cases (n=16), in ovaries - 20% (n=8), in uterine corpus - 12,5% (n=5), in uterine cervix - 15% (n=6), and in vagina - remaining 12,5% (n=5). Average time from diagnosis to beginning of the treatment was 7,5 months. As a result, the onset of specific therapy was delayed in 65% cases (n=26) and 50% (n=20) underwent unneeded surgery. Diagnostic mistakes lead to inadequate treatment. Extranodal non-Hodgkin’s lymphomas of female reproductive system, both primary and secondary, are rare pathology. Primary lesion is more typical for older women, sec- ondary is mainly affecting younger women (in reproductive period). Chemotherapy response and prognosis are better in primary cases.